Context-responsive Approaches of / for Teachers’ Professional Development: A Participatory Framework - Parbati Dhungana; Bal Chandra Luitel; Sigrid Gjøtterud; Shree Krishna Wagle (Journal of Participatory Research Methods)
Reflecting on Participatory Action Research (PAR) experiences in a Nepali community school, this paper showcases how collaborative approaches, such as cross-sectoral, teacher-student, interdisciplinary, and cross-professional action-reflections, created contextually relevant environments for improving teachers’ professional development. Considering the Habermasian Emancipatory interest (1972) as theoretical referents, this paper further explains how teachers’ growing professional autonomy through cross-professional collaboration enhanced their professional agency to integrate curriculum and professional development programs, to practice student-centered pedagogy, and to take on leadership positions. Finally, this paper envisions a participatory framework of and for teachers’ professional development.